Serum levels of soluble receptor for advanced glycation endproducts (sRAGE) are higher in ulcerative colitis and correlate with disease activity - EREN, FATİH; ATUĞ, ÖZLEN; YILMAZ, YUSUF (ELSEVIER SCIENCE BV, 2011)
Interaction of the receptor for advanced glycation endproducts (RAGE) with its ligands results in expression of inflammatory mediators, activation of NF-kappa B, and induction of oxidative stress, all of which have been implicated in the pathogenesis of inflammatory bowel diseases (IBD). Soluble receptor for advanced glycation endproducts (sRAGE) has recently emerged as a reliable biomarker of inflammation in numerous RAGE-mediated disorders. Objective: To assess sRAGE levels in adult patients with IBD. Method: Serum was collected from adult patients with Crohn's disease (CD, 56 patients), ulcerative colitis (UC, 60 patients), and healthy controls (HC, 113 subjects). Levels of sRAGE were determined by enzyme-linked immunosorbent assay. Results: Serum sRAGE levels were elevated in IBD compared to HC and were higher in UC patients compared to CD and HC. Levels of sRAGE were significantly higher in the serum of UC patients with active disease compared to patients with inactive disease, but no association with the Montreal Classification was evident. Serum sRAGE was lower in CD patients with biological therapies. Conclusions: These findings suggest that serum levels of sRAGE are altered in patients with intestinal inflammation and may reflect distinct immunoinflammatory pathogenesis of UC and (C). 2011 European Crohn's and Colitis Organisation. Published by Elsevier B.V. All rights reserved.
Keywords: Crohn's disease; Ulcerative colitis; Receptor for advanced glycation endproducts (RAGE); Enzyme-linked immunosorbent assay; INFLAMMATORY-BOWEL-DISEASE; END-PRODUCTS; RAGE; EXPRESSION; PROTEINS; S100A12; INDEX